PERAN KESADARAN MEREK (BRAND AWARENESS) DALAM MEMEDIASI HUBUNGAN IKLAN OPPO DENGAN NIAT BELI KONSUMEN - Pranata, I Wayan Dicky Reza; Pramudana, Km. Agus Satria (E-Jurnal Manajemen, 2018)
The purpose of this study is to examine the role of brand awareness in mediating advertising relationships with consumers' buying intentions. This research was conducted in Denpasar City. The number of samples taken as many as 105 respondents, with the method of non-probability sampling, especially purposive sampling. Data collection was done through survey method using questionnaire instrument. Data analysis technique used is Path Analysis. Based on the analysis results found that the ads have a positive and significant impact on brand awareness (brand awareness). The study also found that each of the ad variables and brand awareness has a positive and significant impact on consumers' buying intentions. In addition brand awareness (brand awareness) also positively and significantly mediate ad relationship with consumer purchase intention. This indicates that the more interesting the Oppo smartphone ads and the higher brand awareness in the minds of consumers will increase consumer intention to buy on Oppo smartphones. Keywords: advertising, brand awareness purchase intention.